Optimalisasi Penggunaan Model Pembelajaran Picture and Picture Dalam Upaya Meningkatkan Hasil Belajar Siswa Tema Hidup Bersih dan Sehat di Kelas II SD Negeri 206/X Pandan - Yusnani Yusnani (Departement of Mathematics Education, 2021)
This study aims to disclose information and discuss the optimization of the use of the picture and picture learning model in effort to improve student learning outcomes with the theme of clean and healthy living in class II SD Negeri 206/X Pandan Jaya. This research is included in the type of classroom action research (CAR). This research was carried out in this research was carried out at SD Negeri 206/X Pandan Jaya. The time of this research was carried out in the odd semester of the academic year 2021 - 2022, which began in November 2021. The subjects in this study were class II students, totaling 16 people. The research procedure consisted of two cycles with four stages of research starting from planning, implementing, observing, and reflecting. Data collection in this study was carried out using observation, tests, interviews, and documentation. The data were analyzed using the percentage formula. The results of this study indicate that the Picture and Picture Learning Model on the Clean and Healthy Living Theme can improve student learning outcomes in class II SD Negeri 206/X Pandan Jaya which is characterized by increased completeness from pre-cycle (19%), cycle I (25%), cycle II (81%).